Campus, California Polytechnic School, San Luis Obispo, California (E. C. Kropp, 1938)
Color postcard, looking east from Radio Hill towards the main buildings and dormitories at Cal Poly, probably taken around 1938-1941. (The Weeks Administration building, torn down ca. 1940-41, is still standing, and the Crandall Gym Natatorium is visible, which opened in 1938).